MARKET ADAPTATION AND CUSTOMER VALUE IN SMALL ENTERPRISES: LINKING INSIGHT, EXPERIMENTATION, AND STRATEGIC FLEXIBILITY - Diah Fatma Sjoraida; Arif Budi Raharja (Organisasi Kreatif Indonesia Emas, 2025)
This conceptual paper develops an integrative framework for market adaptation and customer value in micro, small, and medium enterprises (MSMEs). It synthesizes established literature on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, resilience, and entrepreneurial ecosystems. The analysis explains how customer insight, market sensing, bounded experimentation, strategic flexibility, and learning-based resource allocation can be organized into proportionate managerial routines. No primary survey, interview, experimental, or statistical data are claimed. The framework proposes problem diagnosis, capability mapping, bounded experimentation, evidence review, governance, resource reconfiguration, and learning retention as a cumulative cycle. Implications are developed for owner-managers, support institutions, and future empirical research.